POST-APPENDECTOMY REHABILITATION: OPTIMAL STRATEGIES FOR AUGMENTED CONVALESCENCE - Komilova Dilrabo Raximboy qizi; Khusainboyev Jamshidbek Davronbekovich; Rustamov Timur Rashidovich (Journal of new century innovations, 2023)
Abstract: Appendectomy, a ubiquitously performed surgical intervention targeting the vermiform appendix, finds its preeminent indication in acute appendicitis. Despite the commonplace nature of appendectomy, the postoperative phase assumes singular importance in shaping patient trajectories. This scientific discourse presents an exhaustive review of convalescence strategies subsequent to appendix excision, accentuating their indispensability in mitigating complications, hastening recovery, and optimizing patient welfare. By means of a methodical analysis of the literature, this article furnishes evidence-anchored insights into the manifold facets of post-appendectomy rehabilitation, spanning from analgesic optimization to early mobilization and alimentary considerations.